Prevalence of Parasitosis in Elderly residents and Workers of Institutions of Long Permanence in the Metropolitan Region of Porto Alegre and the Mountain Region of Rio Grande do Sul - Brandolt Larré, Anne; Duarte Bürgie, Camila; Engroff, Paula; Attilo De Carli, Geraldo (O Mundo da Saúde, 2015)
Despite enteroparasites compromise the nutritional status of the elderly and health care quality in general, studies addressing the occurrence and prevention of intestinal parasites in this population segment are scarce. The scope of this study is to analyze the enteroparasites profile in the elderly and employees working in long-term institutions, correlating them to sociodemographic and economic variables, hygiene habits and symptoms. It is a cross-sectional study in long-term institutions in the Metropolitan Area of Porto Alegre and in the Mountain Region of Rio Grande do Sul. Through the use of questionnaires and collection of stool samples, 12 long-term institutions were searched and 200 stool samples of feces, with an average of 79.4 ± 9.5 years old, were analyzed by Parasitological Examination of Stools. In addition, we collect 26 samples from employees (aged between 19-60 years old). It was found a prevalence of 4.0% of intestinal parasites in relation to the elderly, the higher positivity found in women 4.8% (n=7), while in men 1.8% (n= 1). Of which 75.0% (n=6) corresponded to Endolimax nana and 25.0% (n=2) Entamoeba coli. It was identified in employees, prevalence of 19.2%, of which 60.0% (n=3) accounted for E. nana, 20.0% (n=1) E. coli and 20.0% (n=1) of hyperparasitism. Both regions show peculiar conditions, aging brings some challenges to society, demanding the implementation and effectiveness of social policies of public health congruent to the current reality to improve the life quality for elderly and workers regarding their sociodemographic variables, economic, hygienic habits and symptomatology.